0863 Sleep Behaviors And Patterns In Adult Survivors Of Childhood Cancers: A Report From The Childhood Cancer Survivor Study (CCSS). (27th April 2018) - Daniel, L C; Wang, M; Srivastava, D; Schwartz, L; Brinkman, T; Edelstein, K; Mulrooney, D; Zhou, E; Howell, R; Gibson, T; Leisenring, W; Armstrong, G T; et al.
Abstract: Introduction: Sleep disorders are related to emotional and physical health in the general population; research in childhood cancer survivors is limited. This study characterized sleep behaviors in survivors and examined associations among sleep, cancer diagnoses, treatment exposures, and emotional functioning. Methods: Childhood cancer survivors (≥5 years from diagnosis; n=1933; 50.8% female; mean [SD] age=35.1 [7.6] years; years since diagnosis=23.5 [4.7]) and siblings participants in the CCSS (n=380; 52.4% female; age=33.4 [8.4]) completed sleep quality (Pittsburg Sleep Quality Index), fatigue (Functional Assessment of Chronic Illness Therapy-Fatigue), and sleepiness (Epworth Sleepiness Scale) measures. Emotional functioning was assessed ~5 years before (Behavior Problems Index <18 years old; Brief Symptom Inventory [BSI]>18 years old), and at time of the sleep survey (BSI only). Logistic/log binomial regression models examined relationships among diagnosis, treatment exposures, and emotional functioning on sleep variables, adjusting for age and BMI. Results: In survivors, 35% reported <7-hr sleep duration, 29% reported sleep efficiency <85%, and 18% reported significant daytime sleepiness. Survivors were more likely to report poor sleep efficiency (prevalence ratio [PR] 1.26, 95% confidence interval 1.04–1.53), daytime sleepiness(PR 1.31, 1.01–1.71), and supplement use for sleep(PR 1.56, 1.09–3.60) than siblings. Leukemia survivors reported more delayed sleep onset latency(PR 1.36, 1.01–1.83) compared to bone cancer survivors. Exposure to ≥20 Gy cranial radiation was associated with sleep onset after 1am(PR 2.84, 1.75–4.59) compared to no cranial radiation. Abdominal radiation ≥30 Gy was associated with frequent nighttime awakenings(PR 1.37, 1.08–1.49). Relative to survivors without distress, survivors who developed emotional distress from baseline to follow-up evidenced poor sleep efficiency(PR 1.70, 1.40–2.08), restricted sleep time(PR 1.35, 1.12–1.62), fatigue(PR 2.11, 1.92–2.32), daytime sleepiness(PR 2.19, 1.71–2.82), snoring(PR 1.85, 1.08–3.16), and frequent sleep medication(PR 2.86, 2.00–4.09) and supplement use(PR 1.89, 1.33–2.69). Conclusion: Cancer survivors are more likely to experience poor sleep efficiency, daytime sleepiness, and supplement use than siblings. For survivors who report poor sleep, there is a greater likelihood of persistent or worsened emotional distress; distress management may improve sleep. Support (If Any): NCI U24 CA55727 (PI:Armstrong).